Characterization of Fungal nirK-Containing Communities and N2O Emission From Fungal Denitrification in Arable Soils - Xu, Huifang; Sheng, Rong; Xing, Xiaoyi; Zhang, Wenzhao; Hou, Haijun; Liu, Yi; Qin, Hongling; Chen, Chunlan; Wei, Wenxue (Frontiers in Microbiology, 2019)
Fungal denitrifiers play important roles in soil nitrogen cycling, but we have very limited knowledge about their distribution and functions in ecosystems. In this study, three types of arable soils were collected across different climate zones in China, including quaternary red clay soils, alluvial soils, and black soils. The composition and abundance of fungal nirK-containing denitrifiers was determined by MiSeq high-throughput sequencing and qPCR, respectively. Furthermore, a substrate-induced inhibition approach was used to explore N2O emissions from fungal denitrification. The results showed that the arable soils contained a wide range of nirK-containing fungal denitrifiers, with 4 orders and 8 genera. Additionally, approximately 57.30% of operational taxonomic unit (OTUs) belonged to unclassified nirK-containing fungi. Hypocreales was the most predominant order, with approximately 40.51% of the total number of OTUs, followed by Sordariales, Eurotiales, and Mucorales. It was further indicated that 53% of fungal nirK OTUs were shared by the three types of soils (common), and this group of fungi comprised about 98% of the total relative abundance of the nirK-containing population, indicating that the distribution of fungal nirK-containing denitrifiers was quite homogenous among the soil types. These common OTUs were determined by multiple soil characteristics, while the composition of unique OTUs was manipulated by the specific properties of each soil type. Furthermore, fungal N2O emissions were significantly and positively correlated with fungal nirK abundance in the soils, whereas it was not clearly related to fungal nirK compositions. In conclusion, although the arable soils hosted diverse nirK-containing fungal denitrifiers, fungal nirK compositions were highly homogenous among the soil types, which could be a consequence of enduring agricultural practices. The abundance of fungal nirK-containing denitrifiers, rather than their composition, may play more significant roles in relation to N2O emission from fungal denitrification.